Analisis Total Bakteri Coliform dan Identifikasi Escherichia coli pada Makanan dan Minuman di Kantin X - Irul Hidayati; Reni Ida Wati; Hanik Faizah (Al-Ard: Jurnal Teknik Lingkungan, 2022)
Food is one of the basic necessities of humans. It is important to pay attention to the quality, safety, hygiene and sanitation of food. Healthy food should contain nutrients, vitamins, and the other essential substances for our body need. The food should be safe for consumption, and free from contamination. Food contamination generally occurs due to coliform bacteria contamination that can cause foodborne disease. This study aimed to analyze the total coliform bacteria and identify Escherichia coli bacteria in food and beverage samples in the canteen X. The design of this study was descriptive research. Samples were obtained from four sellers in canteen X. From each seller, one sample of mixed rice and one sample of iced tea were obtained. Samples were analyzed using the MPN (Most Probable Number) method to determine the total coliform bacteria and EMB (Eosin Methylene Blue Agar) media to identify E. coli. The results showed that all food and beverage samples were tested positive for coliform and E. coli with MPN values ​​exceeding the threshold value. The lowest contamination in the food sample was found in the MA1 and MA2 (460 MPN/gram) and the highest contamination was found in the MA3 and MA4 (>1100 MPN/gram), while the lowest contamination in the beverage sample was found in the MI4 (1100 colonies/100 mL), and the highest contamination was found in the MI1, MI2, and MI3 (>2400 colonies/100 mL).